PEMIKIRAN IMAM SYAFI’I DALAM PENDIDIKAN ISLAM DAN URGENSINYA PADA MASA KINI - Mustofa, Khabib; Falakhina , Arum Nela; Cholid, Nur; Zaeni, Rezi Ahamad; Saputra, Alwan Ibnu (Wahana Islamika Jurnal Studi Keislaman, 2025)
In this article, Imam Syafi'i's thoughts on Islamic education and how it is relevant in the current era. Although Imam Shafi'i is known as an expert in jurisprudence, he also made major contributions in the field of education. As reflected in his poetry which prioritizes ethics for those seeking knowledge, he emphasizes the importance of adab (ethics) and akhlak (morals) in the educational curriculum. In this article, Imam Syafi'i's thoughts on education and its relevance for modern education are explored through literature study and content analysis. Research shows that Imam Syafi'i's views on education, especially those related to his emphasis on manners and morals, are still relevant and can make an important contribution to the development of Islamic education that is comprehensive and focuses on building student character. This article also reveals the urgency of Imam Syafi'i's thoughts in Islamic education today. In the modern era full of challenges, Imam Syafi'i's emphasis on manners and morals has become increasingly relevant. Holistic Islamic education, which not only focuses on cognitive aspects but also character development, can be a solution to overcome various social and moral problems faced by society today. Thus, this study does not only provide an academic contribution in understanding Imam Syafi'i's thoughts about education, but also offers views that are relevant and applicable for the development of Islamic education in the present and future.